Computer literacy of physicians among the hospitals of Makkah region - Hani A. S. Shaker; Mian U Farooq (Wolters Kluwer Medknow Publications, 2013)
Background and Objectives: A confidential inquiry by the Directorate General of Health Affairs, Makkah region, Saudi Arabia, found physicians in different hospitals were reluctant to enter patients' related information in electronic medical record systems. One of the major issues raised was that they didn't have the required computer literacy. Our aim, therefore, was to conduct a survey to highlight the computer literacy among the physicians of Makkah region. Materials and Methods: This cross-sectional survey was performed from May to July 2009. A structured questionnaire of four A4 size paper was distributed among the physicians of the Makkah region working in seven different hospitals. The questionnaire contained questions on background knowledge of computers, i.e., (a) basic computer vocabulary knowledge (BCVK) (10 questions), (b) basic computer skills (BCS) (22 questions), (c) basic communication and internet skills (BCIS) (12 questions). Results: Response rate of 368, i.e., 81.6% of sample size (n = 451) was attained. The maximum response came from King Abdul Aziz Hospital (Taif), i.e., 79%. Overall BCVK, BCS and BCIS were the highest among the physicians of Alnoor Specialist Hospital, i.e., 71.3%, 91.4%, 87.7%, respectively. All the hospitals had a satisfactory level of BCVK, but levels of BCS and BCIS were above satisfactory except King Abdul Aziz Hospital (Jeddah) that showed a satisfactory level in BCIS. Conclusion: Majority of the physicians had a good or an excellent level of computer background knowledge that gave a prediction toward the issues of their non-promising attitude and beliefs about electronic data entry.